The Worlds of Russian Village Women : Tradition, Transgression, Compromise - Olson, Laura J., 1962-; Adonʹeva, S. B. (Book collections on Project MUSE., 2012)
Russian rural women have been depicted as victims of oppressive patriarchy, celebrated as symbols of inherent female strength, and extolled as the original source of a great world culture. Throughout the years of collectivization, industrialization, and World War II, women played major roles in the evolution of the Russian village. But how do they see themselves? What do their stories, songs, and customs reveal about their values, desires, and motivations? Based upon nearly three decades of fieldwork, from 1983 to 2010, this book follows three generations of Russian women and shows how they alternately preserve, discard, and rework the cultural traditions of their forebears to suit changing needs and self-conceptions. In a major contribution to the study of folklore, the authors document the ways that women's tales of traditional practices associated with marriage, childbirth, and death reflect both the upholding and the transgression of social norms. Their romance songs, satirical ditties, and healing and harmful magic reveal the complexity of power relations in the Russian villages.